Enhancing technology diffusion in the EU amid tough structural challenges - Matthias Bauer; Elena Sisto; Oscar du Roy (European Centre for International Political Economy (ECIPE), 2024)
To remain globally competitive, the EU must empower firms to adopt the best technology solutions available on global markets. Building on a strong tradition of innovation, the EU relies on corporations across industries to drive the diffusion of technology through the commercialisation of technological innovations. Technology diffusion is crucial for embedding new technologies into society and is essential for sustaining industrial competitiveness. EU and Member State governments must prioritise enhancing the EU's "diffusion capacity" - the ability to effectively spread and adopt innovations across Member States.
Keywords: 330